A simple method to construct circular repeated measurement design classes and efficiently control carry over effects - Riaz M.; Ulhassan M.; Rasheed H.M.K. (Kuwait Journal of Science)
Repeated measurement designs (RMDs) are economical and commonly utilized in pharmacology, psychology, and animal science experiments. However, RMDs might have carryover effects, which become the main source of bias in estimation of treatment effects. Carry over effects can economically be controlled with the use of minimal balanced RMDs, strongly balanced RMDs or their generalized classes. No general procedure is available in literature to obtain these important classes of RMDs. An R-Package has been developed in this article to check the given values v and p for the possible existence of minimal circular balanced and strongly balanced RMDs (along with their generalized classes), generate the sets of shifts for possible designs, and to calculate the efficiency of separability and carry over effects for the generated design. © 2024 The Author(s)